MOTIVASI BELAJAR SELAMA MASA PANDEMI COVID-19 PADA SISWA KELAS V SDN 03 KETAPANG RAYA KECAMATAN KERUAK TAHUN PELAJARAN 2020/2021 - Sp. Nuril Hidayah Al Idrus; H. Hari Witono; Heri Hadi Saputra (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2022)
The purpose of this study was to determine the motivation to learn during the Covid-19 pandemic in fifth grade students at SDN 03 Ketapang Raya, Keruak District, for the 2020/2021 academic year. The results of this study are that the learning motivation of grade V students at SDN 03 Ketapang Raya, Keruak District, East Lombok Regency during the covid-19 pandemic is classified as good, indicated by: 1) Students have shown an attitude of desire and desire to succeed in learning even during the covid-19 pandemic. 19; 2) Students have shown an attitude of encouragement and need in learning; 3) Students have shown an attitude of hope and ideals in the future; 4) Students have shown an attitude of appreciation in learning; 5) Students have shown an attitude of interesting activities in learning during the covid-19 pandemic; 6) Students demonstrate a conducive learning environment during the covid-19 pandemic Keywords: Student Learning Motivation, Covid-19 Pandemic Period